2018
DOI: 10.1002/wat2.1309
|View full text |Cite
|
Sign up to set email alerts
|

Household water sharing: A review of water gifts, exchanges, and transfers across cultures

Abstract: Water sharing offers insight into the everyday and, at times, invisible ties that bind people and households with water and to one another. Water sharing can take many forms, including so-called “pure gifts,” balanced exchanges, and negative reciprocity. In this paper, we examine water sharing between households as a culturally-embedded practice that may be both need-based and symbolically meaningful. Drawing on a wide-ranging review of diverse literatures, we describe how households practice water sharing cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
74
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 109 publications
3
74
0
1
Order By: Relevance
“…As predicted (Wutich et al ), we found a general pattern of more transfers from higher‐status households to lower‐status ones; however, this was not uniformly replicated in every community. In some places, the lowest quintile households were given less water compared to those in higher quintiles.…”
Section: Implications Limitations and Next Stepssupporting
confidence: 81%
See 4 more Smart Citations
“…As predicted (Wutich et al ), we found a general pattern of more transfers from higher‐status households to lower‐status ones; however, this was not uniformly replicated in every community. In some places, the lowest quintile households were given less water compared to those in higher quintiles.…”
Section: Implications Limitations and Next Stepssupporting
confidence: 81%
“…For example, when people collect or buy water for their own household use, it may then be seen as belonging to the person or household that collected or purchased it, regardless of its provenance. As such, another potential form of coping with water shortfalls is the direct sharing of such private water between households; in other words, the acts of giving or receiving water from one household to another as gifts, loans, exchanges, or sales (Wutich and Brewis ; Wutich et al ), sometimes operationally referred to as transfers . By household water sharing , we are referring to transfers of water between households designed to meet daily needs inside the receiving household (i.e., drinking, cooking, sanitation, washing clothes, cleaning, and bathing, but not maintaining livestock or crops).…”
mentioning
confidence: 99%
See 3 more Smart Citations